Situation d'apprentissage et conceptualisation - Pierre Pastré (Nantes Université, 2011)
When we speak of situation, it is important to articulate three concepts: situation, activity, learning. On the one hand, all human activity in a situation unfolds. On the other hand, we learn of situations when they involve a problem, which requires the learner an activity of conceptualization. The text can be divided in two parts: the first part is an epistemological; it proposes a debate between the proponents of the theory of enaction and the supporters of the conceptualization in action, theory which relates the author. The second part, empirical, shows two examples of how professional learnings combine conceptualization and the use of experience.